2013
DOI: 10.5005/jp-journals-10015-1216
|View full text |Cite
|
Sign up to set email alerts
|

A Review of Hypodontia: Classification, Prevalence, Etiology, Associated Anomalies, Clinical Implications and Treatment Options

Abstract: A retrospective review of literature was carried out to determine the classification, prevalence, etiology, associated anomalies, clinical implications and treatment options for hypodontia. Many methods of classification have been reported in the literature. Some researchers have classified hypodontia as isolated family form or as an inherited form; others have defined the congenital absence of teeth according to the number of missing teeth and yet classified hypodontia according to the severity of the conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
33
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 79 publications
3
33
0
2
Order By: Relevance
“…It forms part of the complex adaptive system (CAS) of oro-facial development whereby epithelial tissues and neural crest mesenchyme are involved in delicate signalling pathways with multiple molecular events that overlap each other [1][2][3][4]. For a system to be considered as complex and adaptive, it should exhibit the principles of self-organisation and self-adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…It forms part of the complex adaptive system (CAS) of oro-facial development whereby epithelial tissues and neural crest mesenchyme are involved in delicate signalling pathways with multiple molecular events that overlap each other [1][2][3][4]. For a system to be considered as complex and adaptive, it should exhibit the principles of self-organisation and self-adaptation.…”
Section: Introductionmentioning
confidence: 99%
“…When a specific tooth does not form this is known as tooth agenesis; the most frequently affected teeth are the third molars [1]. The dentition may be affected in varying numbers of missing teeth; hypodontia, which is the absence of one or up to five teeth, oligodontia, which involves six teeth or more and anodontia, which is the total absence of teeth [1]. Oligodontia and anodontia occur infrequently in a population and are commonly associated with syndromes such as ectodermal dysplasia [2].…”
Section: Hypodontiamentioning
confidence: 99%
“…3 Multifactorial etiology combining genetics, epigenetic and environmental factors has been suggested by Al Shahrani et al and Larmour et al 5,6 Regulatory homeobox genes found to be associated with tooth agenesis consist of MSX-1, PAX-9, EDA and AXIN-2. 7 It may also be associated with some environmental insult during development.…”
mentioning
confidence: 99%